PEMBIASAAN MAJELIS SHOLAWAT DA’WATUL KHOIROT DALAM MENANAMKAN NILAI PENDIDIKAN ISLAM - Yusuf, Achmad; Zeynulloh; Masruro, Alfi (Al Ulya: Jurnal Pendidikan Islam, 2022)
Islamic educational values found in Sholawat assembly Da'watul Khoirot in Pilangsari, Beji Village; First, the value of Akidah is reflected in the conduct of the assembly when the process of mauidhoh hasanah caretaker of the assembly teaches us to be confident and trust in God. Chanting sholawat and dhikr together solemnly' as a form of gratitude to Allah and an effort to increase faith in Allah and the Messenger of Allah. Second, the value of worship. The Da'watul Khoirot sholawat assembly consists of the value of mahdah worship and ghairu mahdah. In this assembly, mahdah worship includes congregational tahajud prayers, joint prayers, tadarus reading the qur'an. While ghairu mahdah worship includes silaturrahmi, almsgiving, zikir, bersholawat, seeking knowledge, proselytizing Islam by studying the book of ta'lim muta'allim and wasiyatul musthofa. Third, moral values. the moral values in the Da'watul Khoirot sholawat assembly include the attitude of worshippers who are polite, respectful, greeting, kissing hands to their elders, deliberation, mutual aid and help. Strategies for instilling Islamic educational values for the community in the Da'watul Khoirot Assembly in Pilangsari-Beji village include: Habituation, Exemplary, and Mauidhoh Hasanah